A Constructive Love-Hate Relationship: Modern Theatre Cynics as Theatre Innovators (KULT_online, 2008)
In this study on the anti-theatrical tendency of high modern drama, American comparative literature scholar Martin Puchner unearths an interesting paradox: Armed with examples such as the unstaged plays of Stéphane Mallarmé and Gertrude Stein and the "diegetic theatre" of Bertolt Brecht and Samuel Beckett, Puchner demonstrates how it is the very rejection of a mimetic theatre based on dramatic embodiment that contributes to its renewal. In the process, Puchner brings the concept of (anti-)theatricality to literary modernism and forges a methodological link between the fields of literary and theatre studies.